The Effect of Hanging Ball Media Training on the Overhead Serving Ability of Extracurricular Girls' Volleyball Players at SMP Negeri 36 Rejang Lebong - Ade Kurniawan (Journal of Education, 2026)
This study aims to determine the effect of training using hanging ball media on the upper service ability of female volleyball extracurricular participants at SMP Negeri 36 Rejang Lebong. This type of research is a quasi-experimental with a One Group Pretest-Posttest Design. The sample in this study amounted to 15 female students taken using a total sampling technique. The research instrument used an upper service ability test. The data analysis technique used a t-test. The results showed that the average pre-test score was 18.40 and the average post-test increased to 26.53. Based on the results of the hypothesis test, the value of $t_{count}$ (9.85) > $t_{table}$ (2.145) was obtained at a significance level of 5%. Thus, it can be concluded that there is a significant effect of hanging ball media training on improving the upper service ability of female volleyball extracurricular participants at SMP Negeri 36 Rejang Lebong.